The influence of job variables on repatriates adjustment to the home country / Mahazir Ismail ... [et al.] - Ismail, Mahazir; Harun, Etty Harniza; Farhan Zakaria, Shahida (2015)
The main objective of the present study is to determine the impact of individual variable (self-efficacy), job variables (role clarity, role conflict, role discretion, and role novelty), organizational variable (social support), and nonwork variable (culture novelty) on three dimensions of repatriates ' adjustment (psychological well -being, socio-cultural readjustment, and work readjustment) . Data will be collected from 500 Malaysian repatriates . Four main hypotheses were formulated in order to achieve the objectives of the study. The research and experience of many multinationals show that a formal repatriation and retention program plays a significant role in keeping these valuable resources in the organization. In examining the relationship between the individual variable and repatriates' adjustment, the research will look at individual variable, job variable, organizational variable and non work variable impacted on psychological wellbeing, socio-cultural readjustment and work readjustment among Malaysia repatriates.